Analisis Kepuasan PMIK Terhadap Implementasi Rekam Medis Elektronik dengan Metode EUCS di RSUD Dr. Moewardi - Saryadi Saryadi; Puguh Ika Listyorini; Liss Dyah Dewi Arini; Anggelli Marsha Pattinama (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The implementation of electronic medical records is expected to support the effectiveness of time in service. User satisfaction of electronic medical records, especially PMIK, is an important aspect to determine whether an information system is successful or not. The implementation of electronic medical records at Dr. Moewardi Hospital is still found to be an obstacle, namely when Vclaim is updated in the registration area, it experiences a server error and services are carried out manually, which causes BPJS patient recording and reporting to be carried out twice so that there is inefficiency in work. The purpose of this study is to determine PMIK's satisfaction with the implementation of electronic medical records with the EUCS method at Dr. Moewardi Hospital. This study is a quantitative descriptive research with a cross sectional approach. The data collection technique in this study is a questionnaire. The population in this study is 55 officers. The sampling technique uses total sampling. Data processing in this study is by collecting, editing, coding and presenting data by presenting the research results in the form of tables. Data analysis using univariate analysis. The results of the study show that: 1) The content dimension has a mean value of 4.44, meaning very satisfied. 2) The accuracy dimension has a mean of 4.27, meaning very satisfied. 3) The display dimension (format) has a mean of 4.24, meaning very satisfied. 4) The dimension of ease of use has a mean of 4.20, meaning very satisfied. 5) The timeliness dimension has a mean of 4.26, meaning very satisfied.